Final wishes a cautionary tale of death, dignity and physician-assisted suicide - Chamberlain, Paul 1954- (Downers Grove, IL IVP, 2000)
Includes bibliographical references.
Keywords: Assisted suicide -- United states -- case studies; Terminally ill -- United States -- case studies; Euthanasia -- religious aspects -- Christianity